Praktek Konsep Interaksi Jangka Pendek dalam Pelayanan Kesehatan dan Pengaruhnya terhadap loyalitas Pasien pada Rumah Sakit Umum di Surabaya - Susanti, Christina Esti (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2005)
The general goal of the research is to know the effect of short run interaction concept in medical service to patient loyalty on public hospital in Surabaya. The particular goal of research is to know the effect of: (1) interaction, (2) guaranty, and (3) innovate to medical patient loyalty on public hospital in Surabaya.